None Memimpin Pasar dengan Optimalisasi Distribusi: Formulasi Strategi bagi PT. Avia Avian, Tbk.: None - Novina, Emma; Murhadi, Werner R (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2024)
The aim of this research was to analyze the strategies that companies can adopt to overcome intense market competition. The study focused on strategy formulation, employing a quantitative method that included strategic management steps applicable to PT. Avia Avian, Tbk. in the paint and coatings industry. The research involved examining the company's internal and external environments to identify the strengths, weaknesses, opportunities, and threats (SWOT) of PT. Avia Avian, Tbk. The results of the SWOT analysis were then incorporated into several matrices, including EFE, IFE, CPM, TOWS, SPACE, BCG, IE, GSM, and QSPM. The strategy recommended for PT. Avia Avian, Tbk. was market penetration, considering the global trend of decreasing consumer standards for paint purchases and shifts in national urbanization patterns that favor the company's position. This strategy enables the company to optimize the distribution of its centers throughout Indonesia.